Child soldiers and transitional justice : protecting the rights of children involved in armed conflicts / Bo Viktor Nylund. - Nylund, Bo Viktor (Series on transitional justice ;, 2016)
In a political climate that holds limited promise for addressing the issue of child recruitment, Child Soldiers and Transitional Justice: Protecting the Rights of Children Involved in Armed Conflicts challenges the trend towards a narrow focus on recruitment and use of the child, and seeks to contribute to more effective prevention and responses that offer the child a chance of recovery, reconciliation and reintegration. This book adapts existing theoretical frameworks of transitional justice in order to analyse child recruitment, with a view to demonstrating how a society can address the issue in a holistic way. It systematises relevant knowledge across a wide range of legal fields to allow for greater understanding of the law and principles, and a more informed basis for practical engagement with transitional justice mechanisms.Delving deep into the travaux préparatoires of each of the fundamental legal instruments, the author analyses their evolution, spanning humanitarian law, human rights law, criminal law, and other aspects of public law, including peace agreements and action plans developed with armed groups and forces. He provides a particular focus on and in-depth analysis of the Lubanga case, and its implications for other components of transitional justice. The findings highlight arguments for placing child recruitment firmly on the transitional justice agenda. By considering child recruitment against a transitional justice framework, the book allows a detailed understanding of the distinct but complementary components - rule of law, criminal justice, historical justice, reparatory justice, institutional justice, and participatory justice - and reveals the untapped potential in interactions between different areas of transitional justice.About the authorBo Viktor Nylund is a protection and legal practitioner who has focused on state and non-state actor responsibility and accountability throughout his career. Bo Viktor has Masters degrees in law and political science from Columbia University Law School and Abo Akademi University and a PhD in international law from the Geneva Graduate Institute for International Studies. He has served UNHCR, UNICEF and OHCHR and is currently UNICEF's Representative in Burundi.